Learning Model for Instilling Religious Moderation to Children at an Early Age: A Needs Analysis - Susmiyati, Sri; Saugi, Wildan; Zurqoni; Maesaroh, Dwi Titi (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study investigates the need for a contextual learning model to instill religious moderation values in early childhood education. It aims to explore existing practices, identify gaps, and propose recommendations for developing an integrated instructional framework. Employing a qualitative case study approach, data were collected through in-depth interviews, classroom observations, and documentation at RA Pesantren Ilmu Al-Qur’an, East Kutai, Indonesia. The data were analyzed using Miles and Huberman’s interactive model, focusing on data reduction, data display, and conclusion drawing. The study reveals that values of religious moderation, such as tolerance, inclusivity, and non-violence, are informally practiced through storytelling, modeling, and daily school routines. However, these values are not explicitly incorporated into formal curriculum documents, learning modules, or assessment systems. Teachers expressed a strong need for structured teaching resources, professional development, and assessment instruments aligned with the Merdeka Curriculum to support the systematic development of moderate character in children. The findings underscore the importance of developing a comprehensive, culturally relevant learning model for religious moderation that integrates curriculum design, teacher training, and learning media. Such a model should guide early childhood educators in nurturing tolerance and pluralism from a young age.